2003
DOI: 10.1359/jbmr.2003.18.12.2215
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Risedronate on Regional Bone Metabolism and Blood Flow at the Lumbar Spine Measured by18F-Fluoride Positron Emission Tomography

Abstract: The effect of risedronate on bone metabolism at the lumbar spine was assessed in 18 women who had a 18 F-fluoride PET scan at baseline and after 6 months of therapy. The net plasma clearance of fluoride to bone mineral reflecting osteoblastic activity decreased significantly after therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 29 publications
6
49
0
1
Order By: Relevance
“…(24,25) In contrast to the findings presented here for teriparatide, Frost et al reported an 18% decrease in K i values at the lumbar spine in 18 postmenopausal women treated with risedronate for 6 months. (21) As in the present study, bone blood flow was unchanged, and the decrease in K i was explained by an 18% decrease in k 3 /(k 2 þ k 3 ). In the only other study we are aware of that used 18 F À PET to examine the regional effects of an osteoporosis therapy, Uchida et al reported a 14% decrease in SUVs at the spine and a 24% decrease at the femoral neck in 24 postmenopausal women treated with alendronate for 12 months for glucocorticoid-induced osteoporosis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…(24,25) In contrast to the findings presented here for teriparatide, Frost et al reported an 18% decrease in K i values at the lumbar spine in 18 postmenopausal women treated with risedronate for 6 months. (21) As in the present study, bone blood flow was unchanged, and the decrease in K i was explained by an 18% decrease in k 3 /(k 2 þ k 3 ). In the only other study we are aware of that used 18 F À PET to examine the regional effects of an osteoporosis therapy, Uchida et al reported a 14% decrease in SUVs at the spine and a 24% decrease at the femoral neck in 24 postmenopausal women treated with alendronate for 12 months for glucocorticoid-induced osteoporosis.…”
Section: Discussionsupporting
confidence: 74%
“…Radionuclide imaging provides a novel method of studying regional bone metabolism. (17) One of the most widely used techniques is 18 F-fluoride positron emission tomography ( 18 F À PET) analyzed using the method described by Hawkins et al (18)(19)(20)(21)(22)(23) In the Hawkins method, the bone time-activity curve ORIGINAL ARTICLE J JBMR and the arterial tracer input function are analyzed using a threecompartment model to derive the regional bone plasma clearance (K i : units mL min À1 mL À1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional imaging technique of 18 F-fluoride PET allows a direct quantitative assessment of bone metabolism at specific sites of the skeleton (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In the early 1990s, when 18 F-FDG PET was evolving as a major tool in the field of oncology, 18 F-fluoride PET was introduced as a technique for quantifying bone metabolism by Hawkins et al, who first described the 3-compartmental kinetic model that can be applied in clinical studies (7).…”
mentioning
confidence: 99%
“…(18)(19)(20)(21) The most important role of 18 F-PET is likely to be in clinical drug development, and a number of studies have demonstrated that it is possible to quantify the direct effects of long-term pharmacological treatments for osteoporosis and other metabolic bone diseases on bone formation rate at the spine and hip. (15,(22)(23)(24) The primary objective of this study was to determine if 18 F-PET can be used as an early noninvasive biomarker of treatment efficacy at the hip by examining changes in regional bone formation rate at the proximal femur in a prospective, randomized, and controlled study of postmenopausal women with osteopenia treated with the anabolic agent teriparatide for 12 weeks.…”
Section: Introductionmentioning
confidence: 99%